2020
DOI: 10.1080/17429145.2020.1722266
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical markers for screening salt tolerant quinoa genotypes at early seedling stage

Abstract: The present study was conducted to determine the predictive screening parameters of quinoa salt tolerance that can be applied at early development stages, based on physiological and biochemical approaches. Four quinoa varieties (Tumeko, Red Faro, Kcoito and UDEC-5) were cultivated using hydroponic system, and treated for 2 weeks with different NaCl concentrations (0, 100, 300 and 500 mM). Salt treatment induced a decrease of plant growth depending on NaCl concentrations, plant organs and varieties. Red Faro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Malondialdehyde and hydrogen peroxide (H 2 O 2 ) level enhanced significantly (P ≤ 0.001) under saline conditions in our study (Table 2, Figure 4). Our findings are in accordance with the past studies in rice (Shahbaz et al, 2017) and quinoa (Derbali et al, 2020). Presowing seed treatment with GB prominently (P ≤ 0.001) reduced the both MDA and H 2 O 2 both under nonsaline and saline conditions.…”
Section: Biochemical Attributessupporting
confidence: 93%
“…Malondialdehyde and hydrogen peroxide (H 2 O 2 ) level enhanced significantly (P ≤ 0.001) under saline conditions in our study (Table 2, Figure 4). Our findings are in accordance with the past studies in rice (Shahbaz et al, 2017) and quinoa (Derbali et al, 2020). Presowing seed treatment with GB prominently (P ≤ 0.001) reduced the both MDA and H 2 O 2 both under nonsaline and saline conditions.…”
Section: Biochemical Attributessupporting
confidence: 93%
“…Similarly, Jabeen et al [96] observed a higher amount of MDA content in the roots (44%) than the leaves (38%) compared to the control when Glycine max plants were exposed to 100 mM NaCl. Derbali et al [97] evaluated four genotypes of Chenopodium quinoa (cvs. Tumeko, Red Faro, Kcoito and UDEC-5) under different doses of salt (100, 300 and 500 mM NaCl) and reported that both the MDA and H 2 O 2 contents increased in a dose-dependent manner in these four genotypes.…”
Section: Salinity-induced Oxidative Stress In Plantsmentioning
confidence: 99%
“…There is abundant literature elucidating several mechanisms that contribute to quinoa's high salinity tolerance, and most of them attribute this tolerance to its efficient sodium (Na + ) sequestration in leaf vacuoles, oxidative stress protection, and potassium (K + ) retention (Adolf et al, 2013;Iqbal et al, 2020;Shabala et al, 2012). However, salinity tolerance was shown to widely vary among quinoa cultivars/genotypes (Adolf et al, 2012;Peterson & Murphy, 2015) and between different growth stages (Derbali et al, 2020;Maleki et al,…”
Section: Introductionmentioning
confidence: 99%